Taxonomy, evolution, and biogeography of the rhodniini tribe (Hemiptera: Reduviidae) (2020)
The Triatominae subfamily includes 151 extant and three fossil species. Several species can transmit the protozoan parasite Trypanosoma cruzi, the causative agent of Chagas disease, significantly impacting public health in Latin American countries. The Triatominae can be classified into five tribes, of which the Rhodniini is very important because of its large vector capacity and wide geographical distribution. The Rhodniini tribe comprises 23 (without R. taquarussuensis) species and although several studies have addressed their taxonomy using morphological, morphometric, cytogenetic, and molecular techniques, their evolutionary relationships remain unclear, resulting in inconsistencies at the classification level. Conflicting hypotheses have been proposed regarding the origin, diversification, and identification of these species in Latin America, muddying our understanding of their dispersion and current geographic distribution. Clarifying these factors can help for the design of vector control strategies. The aim of this review is to depict the different approaches used for taxonomy of the Rhodniini and to shed light on their evolution and biogeography. © 2020 by the authors.